Psychological distress in mothers of children admitted to a nutritional rehabilitation unit in Malawi – a comparison with other paediatric wards. Issue 4 (14th November 2013) - Colman, Sarah; Stewart, Robert C; MacArthur, Christine; Kennedy, Neil; Tomenson, Barbara; Creed, Francis
Abstract In a previous study we found a very high prevalence of psychological distress in mothers of children admitted to a nutritional rehabilitation unit (NRU) in Malawi, Africa. The objective of this study was to compare the prevalence and severity of maternal distress within the NRU with that in other paediatric wards. Given the known association between poor maternal psychological well‐being and child undernutrition in low‐ and middle‐income countries, we hypothesised that distress would be higher among NRU mothers. Mothers of consecutive paediatric inpatients in a NRU, a high‐dependency (and research) unit and an oncology ward were assessed for psychological distress using the Self‐Reporting Questionnaire (SRQ). Two hundred sixty‐eight mothers were interviewed (90.3% of eligible). The prevalence of SRQ score ≥8 was 35/150 {23.3% [95% confidence interval (CI) 16.8– 30.9%]} on the NRU, 13/84 [15.5% (95% CI 8.5–25.0%)] on the high‐dependency unit and 7/34 [20.6% (95% CI 8.7–37.9%)] on the oncology ward (χ2 = 2.04, P = 0.36). In linear regression analysis, the correlates of higher SRQ score were child diarrhoea on admission, child diagnosed with tuberculosis, and maternal experience of abuse by partner; child height‐for‐age z‐score fell only just outside significance (P = 0.05). In summary, we found no evidence of greater maternal distress among the mothers of severely malnourished children within the NRU compared with mothers of paediatric inpatients with other severe illnesses. However, in support of previous research findings, we found some evidence that poor maternal psychological well‐being is associated with child stunting and diarrhoea.